2016
DOI: 10.22365/jpsych.2016.274.276
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality therapy in anxiety disorders

Abstract: During the last decade a number of studies have been conducted in order to examine if virtual reality exposure therapy can be an alternative form of therapy for the treatment of mental disorders and particularly for the treatment of anxiety disorders. Imaginal exposure therapy, which is one of the components of Cognitive Behavioral Therapy, cannot be easily applied to all patients and in cases like those virtual reality can be used as an alternative or a supportive psychotherapeutic technique. Most studies usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The joystick/wired gloves are the tool through which the user has the ability to interact and modify the surrounding environment; Through the use of these devices it is detached from the position of mere passive observer becoming active component and responsible for the changes within the virtual space in which it is found catapulted (Villani et al ., 2011). The VRI configuration can also include instruments such as cybertute that provide the user with a feed-back in terms of touch, weight and strength (Mitrusia & Giotakos, 2016).…”
Section: Technologies At the Servicee Of Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…The joystick/wired gloves are the tool through which the user has the ability to interact and modify the surrounding environment; Through the use of these devices it is detached from the position of mere passive observer becoming active component and responsible for the changes within the virtual space in which it is found catapulted (Villani et al ., 2011). The VRI configuration can also include instruments such as cybertute that provide the user with a feed-back in terms of touch, weight and strength (Mitrusia & Giotakos, 2016).…”
Section: Technologies At the Servicee Of Healthmentioning
confidence: 99%
“…The purely experiential nature of this type of application makes it particularly useful in the psychological treatment of different problems. In recent years several studies have demonstrated the efficacy of VR in the psychotherapeutic field in the treatment of phobias (Mitrusia & Giotakos, 2016), social anxiety disorder (Anderson et al ., 2013), post-traumatic stress disorder (Botella et al ., 2015), panic disorder (Perez-Ara, 2010).…”
Section: Technologies At the Servicee Of Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Distraction is a coping strategy based on the management of emotions and thoughts and it shifts the focus of attention from concentrating on unpleasant stimuli to pleasant and interesting stimuli, through a remodeling of the perceived environment. The exposure to VR provides the patient with a large number of sensory stimulations producing distracting effects (Mitrousia & Giotakos ). Studies show that the effectiveness of virtual environments is linked to the sense of presence reported by people who have used VR devices (Witmer & Sing ).…”
mentioning
confidence: 99%